2018
DOI: 10.1002/brb3.1078
|View full text |Cite
|
Sign up to set email alerts
|

Transient topographical disorientation due to right‐sided hippocampal hemorrhage

Abstract: IntroductionTopographical disorientation is defined as the inability to recognize familiar or unfamiliar environments. While its slowly progressive development is a common feature of neurodegenerative processes like Alzheimer's dementia, acute presentations are less frequent and mostly caused by strategic lesions within the cerebral navigation network. Depending on the lesion site, topographical disorientation can originate from deficits in landmark recognition and utilization for route planning (egocentric na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The right PHG has been repeatedly linked to topographical disorientation 14,15 . It has been suggested that the PHG plays an important role in egocentric and allocentric orientation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The right PHG has been repeatedly linked to topographical disorientation 14,15 . It has been suggested that the PHG plays an important role in egocentric and allocentric orientation.…”
Section: Discussionmentioning
confidence: 99%
“…The right PHG has been repeatedly linked to topographical disorientation. 14 , 15 It has been suggested that the PHG plays an important role in egocentric and allocentric orientation. For example, patients with right‐sided posterior PHG lesions are impaired on a task involving allocentric orientation, for example, a virtual maze acquisition task.…”
Section: Discussionmentioning
confidence: 99%
“…Vestibular symptoms such as dizziness are among the most common symptoms accompanying transient global amnesia and transient topographical disorientation due to hippocampal lesions. 41,42 CalORIC vesTIbUlaR sTImUlaTION CVS as developed by the otologist Robert Bárány revolutionized clinical vestibular research. 43 This has recently become a popular research tool again, especially for studying the vestibular cortex.…”
Section: Cingulate Cortexmentioning
confidence: 99%
“…These tests cannot distinguish between deficits due to general cognitive and memory impairments, and specific deficits from sensorimotor degradation that then impact the establishment of the mental models or cognitive maps necessary for orientation in space. Clinical tests involving navigation in real environments have detected differential navigational deficits in allocentric and egocentric space [6]. However, these tests are not widely available and we just beginning to understand the systematic read-out parameters that can be extracted in real navigation paradigms [7].…”
Section: Introductionmentioning
confidence: 99%